(untitled) - Finch, Geoffrey (New York, N.Y., 2003)
This is a popular introduction to language and communication written for those with a general or academic interest in the field. Geoffrey Finch introduces readers to current debates about the evolution, structure, psychology, and function of language in a lively, accessible, and jargon-free way. The book focuses on various issues and topics in the study of language, such as communication, media, structure, and society, rather than on linguistic concepts per se, and assumes no prior knowledge of language study.
Keywords: Language and languages,Linguistics